The behavior code companion : stategies, tools, and interventions for supporting students with anxiety-related or oppositional behaviors - Minahan, Jessica (Cambridge, Massachusetts : Harvard Education Press, 2015)
Since its publication in 2012, The Behavior Code: A Practical Guide to Understanding and Teaching the Most Challenging Students has helped countless classroom teachers, special educators, and others implement an effective, new approach to teaching focused on skill-building, practical interventions, and purposeful, positive interactions with students who have mental health disorders. Based on the success of the previous book, author Jessica Minahan has written this companion guide for educators seeking additional guidance for creating and implementing successful behavior intervention plans ((3z(BFAIR Plans(3y(B) for the students teachers worry about the most: those with anxiety-related or oppositional behaviors. Minahan takes readers step-by-step through the process of understanding and practicing the components of a FAIR behavior intervention plan so that they or a team can immediately customize it and put it to work in classrooms. Additional tips on creating interventions, as well as checklists to help with implementation and monitoring progress, are also included. Packed with brainstorming and reflection exercises, planning activities, templates, case studies, recommended apps, and other technology resources, The Behavior Code Companion will help educators create optimal classroom environments for all students.s
1. Cracking the code: embracing a new perspective on behavior -- 2. The FAIR behavior intervention plan : practicing the fundamentals -- 3. Key interventions for successfully supporting students -- 4. Get away from me: strategies and interventions for students with anxiety-related behaviors -- 5. You're not the boss of me: strategies and interventions for student with oppositional behavior -- 6. Creating FAIR behavior intervention plans -- 7. Tools for monitoring progress and implementation -- Appendix A: Individualized education program goals and objectives.
Includes bibliographical references and index.
Keywords: SCHOOL DISCIPLINE